PENGGUNAAN MEDIA KARTU BERGAMBAR DALAM PENGEMBANGAN MATERI AJAR BUKU HANYU TINGLI JIAOCHENG UNTUK MATA KULIAH MENYIMAK I DAN II BAHASA MANDARIN - Rizky Wardhani (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2015)
This research focused on the study on the development of teaching materials using the instructional media card with a picture in a book “Hanyu Tingli Jiaocheng” especially vocabulary as supporting the learning process. The choosing of appropriate learning media supported the teaching-learning process. The choosing of the media must be done carefully using many considerations to achieve the target of learning in facilitating the learners. This research was conducted on the Mandarin Listening I and II. Approproate teaching materials are needed to support teachers who teach this course. This study used qualitative research. The research was done in the Basic Class I and Basic Class II. The result showed that the Mandarin students got new concept for Mandarin learning process.